2003
DOI: 10.1007/s10103-003-0258-6
|View full text |Cite
|
Sign up to set email alerts
|

No effect of GA-AS (904 nm) laser irradiation on the intact skin of the injured rat sciatic nerve

Abstract: We evaluated the electrophysiological and histopathological effects of low-energy gallium arsenide (904 nm) laser irradiation on the intact skin injured rat sciatic nerve. Twenty-four male Wistar rats were divided into three groups ( n=8 each). At the level of proximal third of the femur the sciatic nerve was crushed bilaterally with an aneurysm clip (Aesculap FE 751, Tuttingen, Germany) for half a second. A gallium arsenide laser (wavelength 904 nm, pulse duration 220 ns, peak power per pulse 27 W, spot size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 16 publications
1
31
0
3
Order By: Relevance
“…17 Rochkind et al 17 , Khullar et al 6 and Gigo-Benato et al 13 studied the influence of low-intensity laser, irradiated along the nerve path, on peripheral nerve injuries and found positive effects for nerve regeneration. In studying low-intensity laser irradiation in the spinal cord, in the region corresponding to the injured nerve, Rochkind et al 4 reported an improvement in the recovery of the corresponding injured peripheral nerve, while Bagis et al, 5 in conducting a study with the crushing of rat sciatic nerves, used the same irradiation site with the GaAs laser and declared that it is inefficient in the repair of nerve lesions. In the study by Bagis et al 5 two factors might have influenced the fact that no improvement was found in nerve regeneration, the probably short application time of the laser in seven consecutive days, and the pulsed emission of the low-intensity laser chosen for the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Rochkind et al 17 , Khullar et al 6 and Gigo-Benato et al 13 studied the influence of low-intensity laser, irradiated along the nerve path, on peripheral nerve injuries and found positive effects for nerve regeneration. In studying low-intensity laser irradiation in the spinal cord, in the region corresponding to the injured nerve, Rochkind et al 4 reported an improvement in the recovery of the corresponding injured peripheral nerve, while Bagis et al, 5 in conducting a study with the crushing of rat sciatic nerves, used the same irradiation site with the GaAs laser and declared that it is inefficient in the repair of nerve lesions. In the study by Bagis et al 5 two factors might have influenced the fact that no improvement was found in nerve regeneration, the probably short application time of the laser in seven consecutive days, and the pulsed emission of the low-intensity laser chosen for the study.…”
Section: Discussionmentioning
confidence: 99%
“…In studying low-intensity laser irradiation in the spinal cord, in the region corresponding to the injured nerve, Rochkind et al 4 reported an improvement in the recovery of the corresponding injured peripheral nerve, while Bagis et al, 5 in conducting a study with the crushing of rat sciatic nerves, used the same irradiation site with the GaAs laser and declared that it is inefficient in the repair of nerve lesions. In the study by Bagis et al 5 two factors might have influenced the fact that no improvement was found in nerve regeneration, the probably short application time of the laser in seven consecutive days, and the pulsed emission of the low-intensity laser chosen for the study. Anders et al 3 proposed that the effect of low-intensity laser beams on peripheral nerve recovery can be increased if both the nerve path and the corresponding segment of the spinal cord are irradiated.…”
Section: Discussionmentioning
confidence: 99%
“…19 Since then, many other studies on the effect of different wavelengths of LLLT on slight and mild peripheral nerve lesion have been reported. 14,[20][21][22][23][24][25] In addition, combination of laser therapy with entubulation to reconstruct massive segmental loss of peripheral nerve has shown very promising outcomes. [26][27][28] Most reports on the effect of LLLT on PNS injury are in cases of axonotmesis.…”
Section: Introductionmentioning
confidence: 99%
“…It may be presumed that there were differences in the obtained results because the samples were not identical. However, Bagis et al 25 also studied the effect of laser energy on the nerve tissue of rats and did not obtain significant results, using ΔEs between 0.31 and 19 J/cm 2 and energy levels between 0.09 and 5.3 J. To reach these final energy values, the authors used a prolonged application time (900s) for their equipment with a low Pm (0.02-0.08 mW).…”
Section: Resultsmentioning
confidence: 99%